Virtual Human Models for Electromagnetic Studies and Their Applications - Makarov, Sergey N.; Noetscher, Gregory M.; Yanamadala, Janakinadh; Piazza, Matthew W.; Louie, Sara; Prokop, Alexander; Nazarian, Ara; Nummenmaa, Aapo (IEEE reviews in biomedical engineering, 2017)
Numerical simulation of electromagnetic, thermal, and mechanical responses of the human body to different stimuli in magnetic resonance imaging safety, antenna research, electromagnetic tomography, and electromagnetic stimulation is currently limited by the availability of anatomically adequate and numerically efficient cross-platform computational models or "virtual humans." The objective of this study is to provide a comprehensive review of modern human models and body region models available in the field and their important features.